Arsenic Adsorption Characteristics of Adsorbent Prepared From Spinacia oleracea (Spinach) Leaves - Jha, Prakash Kumar; Jha, Vinay Kumar (Scientific World, 2021)
The dry spinach leaves fine powder was modified by activation with conc. H2SO4 and the adsorbent material was then characterized by using FTIR, EDX, optical microscopy, XRD analysis and methylene blue adsorption method. The EDX result showed about 95 % carbon in the adsorbent material. The maximum specific surface area measured was 499 m2/g. The weak and broad XRD diffraction peaks at 2θ angles 20.5 and 42° were characterized as of activated carbon with the appearance of sharp peak of SiO2 at 2θ angle 26.37°. Optical microscopy Image analysis showed the Porous nature of adsorbents. The adsorption of arsenite on the modified spinach leaves powder adsorbent was investigated by varying different experimental parameters such as pH, adsorbent dose, contact time and As (Ⅲ) ion concentration. The adsorption process was found to be best fitted to Langmuir adsorption isotherm model controlled by pseudo-second–order kinetics with the rate constant value 0.01830 g/(mg·min). The maximum adsorption was observed at pH 6 at room temperature. The maximum adsorption capacity for As (Ⅲ) on modified spinach leaves powder was found to be 58.480 mg/g. The value of ∆G was -22 kJ/mole which confirmed the adsorption process was favored by physisorption. The slope of the linear plot of Qt vs t0.5 was linear but not passed through the origin, which indicates that, the intraparticle diffusion was not only rate controlling step.